Effect of D168V mutation in NS3/4A HCV protease on susceptibilities of faldaprevir and danoprevir - Meeprasert A. (2017)
© The Royal Society of Chemistry. Hepatitis C virus (HCV) is a serious cause of liver inflammation, cirrhosis and the development of hepatocellular carcinoma. Its NS3/4A serine protease functions to cleave a specific peptide bond, which is an important step in HCV replication. Thus the NS3/4A protease has become one of the main drug-targets in the design and development of anti-HCV agents. Unfortunately, high mutation rates in HCV have been reported due to the lack of RNA proofreading activity resulting in drug resistance. Herein, all-atom molecular dynamics simulations were employed to understand and illustrate the effects of the NS3/4A D168V mutation on faldaprevir (FDV) and danoprevir (DNV) binding efficiency. The D168V mutation was shown to interrupt the hydrogen bonding network of Q80R155D168R123 embedded in the extended S2 and partial S4 subsites of the NS3 protein and as a result the R123 side chain was displaced and moved out from the binding pocket. By means of MM/PBSA and MM/GBSA binding free energy calculations, the FDV and DNV binding affinities were shown to be significantly reduced by ∼10-15 kcal mol 1 and ∼4-9 kcal mol 1 relative to the wild-type complexes, respectively, which somewhat agrees with the experimental resistance folds.